2002
DOI: 10.3758/bf03194960
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent activation of high- and low-level production processes in written composition

Abstract: Writing a text requires the coordination of multiple high-level composition processes in working memory, including planning, language generation, and reviewing, in addition to low-level motor transcription. Here, interference in reaction time (RT) for detecting auditory probes was used to measure the attentional demands of (1) copying in longhand a prepared text (transcription), (2) composing a text and pausing handwriting for longer than 250 msec (composition), and (3) composing and currently handwriting (tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
122
0
8

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 171 publications
(148 citation statements)
references
References 15 publications
9
122
0
8
Order By: Relevance
“…It takes a long time to become proficient in transcription and there is evidence that this might only fully happen towards age 14 (Alves & Limpo, 2015a;Chartrel & Vinter, 2004Graham et al, 1998;Pontart et al, 2013). More TRANSCRIPTION-WRITING LINK 5 efficient transcription allows children to start coordinating other writing processes in parallel rather than in sequence (Olive & Kellogg, 2002). That is, once transcription stops depleting attentional resources, children are able to sustain transcription concurrently with planning and translating processes during text production, instead of activating one process at a time (for a review on parallel vs. sequential processing in writing, see Olive, 2014).…”
Section: Transcription-writing Linkmentioning
confidence: 99%
See 2 more Smart Citations
“…It takes a long time to become proficient in transcription and there is evidence that this might only fully happen towards age 14 (Alves & Limpo, 2015a;Chartrel & Vinter, 2004Graham et al, 1998;Pontart et al, 2013). More TRANSCRIPTION-WRITING LINK 5 efficient transcription allows children to start coordinating other writing processes in parallel rather than in sequence (Olive & Kellogg, 2002). That is, once transcription stops depleting attentional resources, children are able to sustain transcription concurrently with planning and translating processes during text production, instead of activating one process at a time (for a review on parallel vs. sequential processing in writing, see Olive, 2014).…”
Section: Transcription-writing Linkmentioning
confidence: 99%
“…It is generally assumed that in novice writers, handwriting and spelling drain attentional resources from high-level writing processes fundamental to produce good texts, such as planning ideas or translating them into language (Bourdin & Fayol, 1994;Fayol, 1999;Kellogg, 1996;McCutchen, 2006;Olive & Kellogg, 2002). Poor transcription skills may constrain planning and translating processes in several ways.…”
Section: Transcription Constrains Planning and Translatingmentioning
confidence: 99%
See 1 more Smart Citation
“…Vanderberg and Swanson (2007) showed that the central executive significantly predicted planning, translating, and revising, as well as vocabulary, punctuation, text structure, and grammar (beta weights ranged from .21 to .32). As transcription and self-regulation compete for the same pool of attentional resources, these processes must be juggled to manage cognitive load (Alamargot, Plane, Lambert, & Chesnet, 2010;Berninger, 1999;Fayol, 1999;Kellogg, 1996;McCutchen, 1996).…”
Section: Transcription Competes With Self-regulationmentioning
confidence: 99%
“…Skills to write legibly are evaluated separately. In literature (Berninger, 1999;Santangelo & Graham, 2015;Olive & Kellog, 2002), it is claimed that success in handwriting affects success in written expression. This study has found out that students' scores for legible handwriting are good while their scores for written expression is moderate.…”
Section: Discussionmentioning
confidence: 99%